On the relation between income inequality and happiness: do fairness perceptions matter? - Bjørnskov, Christian; Dreher, Axel; Fischer, Justina A. V.; Schnellenbach, Jan (Discussion paper series, 2010)
In this paper, we revisit the association between happiness and inequality. We argue that the perceived fairness of the income generation process affects this association. Building on a two-period model of individual life-time utility maximization, we predict that persons with higher perceived fairness will experience higher levels of life-time utility and are less in favor of income redistribution. In societies with a high level of actual social mobility, income inequality is perceived more positively with increased expected fairness. The opposite is expected for countries with low actual social mobility, due to an increasing relevance of a disappointment effect resulting from unsuccessful individual investments. Using the World Values Survey data and a broad set of fairness measures, we find strong support for the negative (positive) association between fairness perceptions and the demand for more equal incomes (subjective well-being). We also find strong empirical support for the disappointment effect in low social mobility countries. In contrast, the results for high-mobility countries turn out to be ambiguous.